The Role of E-Trust in Mediating the Relationship between Online Shopping Experience and E-WOM on Loyalty - Endang Tjahjaningsih; Sri Isnowati; Alya Takwarina Cahyani; Siti Farhana Zakaria (Media Ekonomi dan Manajemen, 2024)
The study's objectives are to use e-trust to boost loyalty while investigating how online shopping experiences and electronic word-of-mouth affect e-trust. Utilizing a quantitative methodology, online surveys are used to gather data for the study. The target market consists of online shoppers at Kimtzu. Id, Shoppe market residents of Semarang City, Indonesia. Targeting participants was done through purposeful sampling, resulting in a sample size of 150 Kimtzu ID consumers. Structural Equation Modeling-Amos is the analysis method used. This study discovered empirical evidence supporting the positive effects of electronic word-of-mouth and online purchasing experiences on e-trust and loyalty. Empirical data demonstrates that e-trust has an effect on boosting loyalty and that it mediates the influence of electronic word-of-mouth and online purchasing experiences on loyalty. Therefore, as a mediating factor between the online purchasing experience and electronic word of mouth, e-trust significantly impacts loyalty. Building trust in the context of loyalty is the role of e-trust, which is a crucial component of the online buying system.